Analisis karakteristik pembeli online anggota kaskus.us dalam proses pembelian online : Studi kasus: FJB kaskus.us - Ardikoesoema, Nurmansyah (Institute for Advanced Science, Social, and Sustainable Future, 2024)
This research uses descriptive quantitative methods as a theoretical basis to test perceptions of ease of use as well as perceptions of benefits accompanied by external variables, namely trust, in influencing the intention of Kaskus.us members to make purchases at the Kaskus.us Buying and Selling Forum. The population in this study were all Kaskus.us members who had posted any information on the Kaskus.us Buying and Selling Forum. The research methods used were purposive sampling and convenience sampling with structural equation modeling (SEM) analysis techniques. There were 200 respondents who generally stated that trust had a significant effect on online purchasing intentions. The research results also show that ease of use and benefits have a significant effect on online purchasing intentions at the Kaskus.us Buying and Selling Forum. Overall, this research aims to analyze the influence of perceived ease of use, perceived usefulness, and trust on the intention to make online purchases among Kaskus.us members. By using 200 respondents who are active members of the Kaskus.us Buying and Selling Forum, they were involved. The results show that trust, ease of use, and perceived usefulness significantly influence respondents' intention to make online purchases through the platform.